2015
DOI: 10.1016/j.applthermaleng.2015.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Numerically-based parametric analysis of plain fin and tube compact heat exchangers

Abstract: In the present study, the hydrodynamic and heat transfer characteristics of six-tube-row compact fin and tube heat exchangers have been investigated numerically by introducing a methodology of analysis based on local and global energy balances, from three-dimensional velocity and temperature fields. The aim is to analyze the influence of operating conditions and the geometry to design more efficient devices. Tube diameter, fin spacing and tube layout are the geometrical parameters; the over-tube fluid velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The governing equations were discretized on the computational domain, which is the minimum required to accurately resemble the entire system and ensure accurate results while maintaining a manageable CPU time [26,27]. for both the fluid flow inside the channel and the TLC-Mylar layer, and solved by the well-known finite element method using the general software COMSOL Multiphysics (http://www.comsol.com).…”
Section: Discretization Methodsmentioning
confidence: 99%
“…The governing equations were discretized on the computational domain, which is the minimum required to accurately resemble the entire system and ensure accurate results while maintaining a manageable CPU time [26,27]. for both the fluid flow inside the channel and the TLC-Mylar layer, and solved by the well-known finite element method using the general software COMSOL Multiphysics (http://www.comsol.com).…”
Section: Discretization Methodsmentioning
confidence: 99%
“…More precisely, the melting and solidification processes have been numerically studied to determine an accurate model for describing the charging and discharging of the system. The study presented in [17] conducts a numerical investigation of the hydrodynamics and heat transfer of a six-tube-row compact fin and tube heat exchangers. The aim of the analysis was to identify the interaction between the geometry and the operating conditions to design more efficient devices.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that fin tubes at the downstream region contribute to high heat exchange efficiency. Based on the local and global energy balances analysis method, Cobian-Iñiguez et al [ 14 ] developed a 3D model to study the characteristic of compact finned tube heat sink with six tube rows. Their study emphasized the influence of operating conditions and the geometry and reporting changes in flow velocity considerably affected temperature fields and thermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…5.86 (0 kPa < p < 25 kPa)(13) h = 2.2895(p/p 0 ) −0.0328 Re 0.7816 Pr 8.39 (25 kPa ≤ p < 101 kPa)(14) where p is equal to the environment pressur, and p 0 is the normal pressure of 101 kPa. = 0.04588Re −0.1425 (p/p 0 )0.0134 (200 < Re < 11136) (16) f = 76.4078Re −0.99738 (p/p 0 ) −0.01076 (Re < 500) (17) f = 2.8069Re −0.47 (p/p 0 ) −0.0063 (500 ≤ Re < 11136)…”
mentioning
confidence: 99%